Refining definitions of periodontal disease and caries for prediction models of incident tooth loss - Houshmand, Mohammad; Holtfreter, Birte; Berg, Marie Henrike; Schwahn, Christian; Meisel, Peter; Biffar, Reiner; Kindler, Stefan; Kocher, Thomas (Journal of clinical periodontology, 2012)
Aim To assess the suitability of different definitions of caries and periodontitis for inclusion in tooth loss prediction models. Materials and Methods The Study of Health in Pomerania (SHIP) is a population‐based cohort study conducted in 1997–2001 (SHIP‐0) and 2002–2006 (SHIP‐1). This sample comprised 2,780 subjects aged 20–81 years with complete information on dental and periodontal status [DMFS status, clinical attachment loss (CAL) and probing depth (PD)]. Analyses on five‐year tooth loss were limited to half‐mouth data. Results The predictive value of tested definitions was markedly age‐ and gender‐dependent: in 20–39‐aged men, the number of decayed or filled surfaces best predicted the number of lost teeth, whereas in young women CAL≥4 mm performed best. In older subjects, periodontal definitions were superior to caries definitions: mean CAL performed best in 40–59‐year olds, whereas AL‐ or PD‐related definitions predicted best in 60–81‐year olds. On tooth level, mean CAL was the superior definition to assess 5‐year incident tooth loss in all strata except for young men. Conclusions Caries parameters best predicted incident tooth loss in men aged 20–39 years; in the intermediate and oldest age group and in young women, mean AL was most informative. Therefore, prediction models need to be developed for different age and gender groups.